The paradox of graduate programs in Reading Education in the Philippines amid a literacy crisis - Gatcho, Al Ryanne Gabonada; Sali, Fatima Zahra Vercede (Frontiers in Education, 2026)
The Philippines faces a paradox in advancing literacy education. Even as the nation confronts a deepening literacy crisis, graduate programs in Reading Education, established to train literacy leaders, operate under fragile conditions. Their expansion has been shaped less by disciplinary strength than by three forces: the scarcity of Reading-trained faculty, policy incentives that reward proliferation over rigor, and institutional survival strategies that privilege prestige and enrollment. These dynamics erode the quality of the discipline, compromise student preparation, weaken system capacity, and diminish trust in graduate credentials. Yet the crisis also presents opportunity. Strengthened faculty development, interuniversity collaboration, rigorous accreditation standards, and recognition of Reading Education as a national investment can transform these programs into credible engines of reform. The Philippine case contributes to the comparative higher education research agenda by illustrating how program growth in specialized fields risks undermining disciplinary integrity when not matched by faculty capacity and institutional safeguards.